Síntese e avaliação da atividade biológica de novos desoxinucleosídeos quinolônicos, ribonucleosídeos pirimido[5,4-c]quinolínicos e novos derivados quinolônicos contendo substituintes triazólicos - Santos, Carla Verônica Baptista dos (2004)
In the present work the 6 and 7 substituted 3-carboethoxy-4(1H)-quinolones 98a-98o (fluorine, chlorine, bromine, iodine, methyl, methoxy and nitro) were synthesized in 72-87% yields. These quinolones were silylated by using bis-(trimethyl)trifluoroacetamide (BSTFA). Glycosylation of these silylated heterocycles was accomplished by their treatment with 1-O-acetyl-2,3,5-tri-O-benzoyl-β-D-ribofuranose (49) in the presence of Trimethylsilyltrifluoromethanesulphonate ( TMSO-Tf), providing the desired ribonucleosides 3-carboethoxy-1-(2,3,5-tri-O-benzoyl-β-D-ribofuranosyl)- 4(1H)-quinolones 99a-99o, in 65-89% yields. The de-O-benzoylation reaction of 99, using methanolic sodium carbonate solution led to the new 3-carbomethoxy-1- β-D-ribofuranosyl)- 4(1H)-quinolones 100 in 70-77% yields. The 6-F,Cl, Br, Me and 7-F-ribonucleosides 100 were used as precursors in the synthesis of their respective bromoacethylated derivatives 90. In these reactions, the bromoacetylation of 100 (6-Cl, Br and Me) yielded the corresponding mixture of regioisomeric bromoacetates 3 (2 )-Br, 2 (3 )-O-acetyl, being 2 -O-acetyl-3 -Br derivative the majoritary one ( 3:1, 5:1 and 3:1, respectively). This reaction when applied to 6-fluoro and 7-fluoro ribonucleosides 100a and 100f afforded the corresponding 2 ,3 ,5 -tri-O-acetylated derivatives. However, the same reaction when using 6-methyl-1-β-D-ribofuranosyl-4(1H)-quinolone-3-carboxylic acid (100m) as the starting material produced the new 6-methyl-1-(2 ,5 -di-O-acetyl-3 -bromo-3 -deoxy-β-D-ribofuranosyl-4(1H)quinolone-3-carboxylic acid (90e) as the only regioisomer in 65% yield. The β-Elimination reactions with these bromo-O-acetylated nucleosides were attempted by two methodologies. The first one using zinc-copper alloy in DMF and the second one using lithium in THF under ultrasound. These reactions failed to give the olefinec products. However, when the pure bromoacetate 90e was reacted with zinc-copper alloy, in DMF, under ultrasound, the desired 2`.3`-didesydrodidesoxy ribonucleoside was obtained. Regioselective deprotection of 2 ,3 ,5 -tri-O-benzoylated nucleosides 99 by using sodium methoxide in THF led to the new 5 -O-benzoylated ribonucleosides 103a-103c in good yields. These substances were employed in attempts to obtain 2 ,3 -cyclic thiocarbonates or to obtain 2 ,3 -bisxanthates, unsuccessfuly. In the search for new heterocyclic nucleosides having pyrimidoquinoline ring, with potential antiviral activity, the quinolones 98 were reacted with urea or thiourea in sodium hydroxide solution leding only to the product in which the ester moiety of the starting material was hydrolyzed The same procedure was applied to the nucleosides 99 affording the ribonucleosides 100 in which all the ester groups of the protected ribonucleosides XV were hydrolyzed (59-76% yields). Additional efforts to obtain new pyrimidoquinoline derivatives were done. The quinolones 98 were alkylated with ethyl bromide in DMF producing the corresponding N-ethylquinolones 108 in 74-84% yields. Subsequently basic hydrolysis of the esther group at C3 led to carboxylic acids derivatives XXI in 62-80% yields. The condensation of 108f (R=6-OMe) with thiourea in the presence of sodium carbonate resulted in the isolation of the new heterocycle 6-ethyl-9-methoxy-4-oxo-2-thione-2,3,4,6-tetrahydropyrimido[5,4-c]quinoline (94), in 72% yield. In the search of new quinolonic derivatives containing the tryazolic nucleous as substituint the aminoquinolones 108o and 108p were synthesized in 70 and 72% yields respectively, by reduction of the nitroquinolones 108g and 108n. In the first approach the amines were reacted with 1,3-dicaronylcompounds aiming to obtain the corresponding enamino esters, which would produce the tryazolic ring. However, this reaction failed to give the desired product. In order to overcome this problem, the aminoacrylate 104p was synthesized (75% yield), and subsequently reacted with diazomalonaldehyde forming the tryazolic moiety, followed by a condensation reaction leading to the iminoderivative (119), in 75% yield, which was hydrolyzed, under acid conditions, giving the tryazolic acrylate 118, in 65% yield.